The choice of proton pump inhibitor from the standpoint of efficacy and safety in a particular patient - E. A. Lyalukova; Yu. V. Tereschenko; E. N. Chernysheva; A. V. Lyalukov (Лечащий Врач, 2021)
Proton pump inhibitors are a diverse class of drugs with unique acid suppression properties. The aim of the work was to present the therapeutic benefits of rabeprazole and pantoprazole in clinical practice. Numerous studies have demonstrated the high effectiveness of proton pump inhibitors and the relative safety of taking these drugs. However, it is necessary to increase the awareness of doctors and pharmacists regarding the possibility of complications during treatment with proton pump inhibitors in a polymorbid patient. The choice of proton pump inhibitors should be based on the clinical situation, concomitant pathology and therapy, the presence of risk factors in the patient, the speed and stability of the effect of the drug. Rabeprazole is converted from prodrug to drug faster than other drugs, and thus creates a greater gradient of prodrug concentration on the membrane secretory tubules. The pharmacodynamics of rabeprazole does not depend on gene polymorphism; in this regard, there is no need for dose adjustment in fast metabolizers. In addition, a distinctive feature of rabeprazole is the ability to more stimulate the production of mucin, thereby providing an additional cytoprotective effect.A feature of the metabolism of pantoprazole is that in addition to binding to cysteine 813, there is an additional connection with cysteine 822, which ensures the restoration of acid secretion only the synthesis of a new protein and, as a result, the longest lasting effect of the drug. High pH selectivity characterizes the low probability of inhibition of proton pumps in tissues with a less acidic pH, i.e. determines the specificity of action only in the parietal cells of the stomach and the greatest safety of long-term use in patients with comorbid pathology. Among all proton pump inhibitors, pantoprazole and rabeprazole have the lowest affinity for the cytochrome P450 system and lower inhibitory activity against CYP2C19, demonstrating a minimal risk of drug interactions.